2022
DOI: 10.3390/life12050767
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Effect of Phellodendron amurense Rupr. Based on Angiogenesis

Abstract: Phellodendron amurense Rupr. is medicinal plant used for supplemental therapy of various diseases based on their positive biological activities. The aim of this study was evaluated the main metabolite, safety of application and anticancer potential. Berberine was determined by HPLC as main alkaloid. Harmful character was determined by irritation test in ovo. The potential cancerogenic effect was studied in vitro on a cellular level, in ovo by CAM assay and in vivo on whole organism Artemia franciscana. Extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…amurense is one of the major plants in traditional Chinese medicine. It has been used traditionally in folk medicine for hepatitis, dysentery, and gynaecological inflammation [68]. P. amurense contains mainly isoquinoline alkaloids, such as berberine chloride [69].…”
Section: Phellodendron Amurensementioning
confidence: 99%
“…amurense is one of the major plants in traditional Chinese medicine. It has been used traditionally in folk medicine for hepatitis, dysentery, and gynaecological inflammation [68]. P. amurense contains mainly isoquinoline alkaloids, such as berberine chloride [69].…”
Section: Phellodendron Amurensementioning
confidence: 99%
“…The deciduous tree is enriched in various chemical compounds such as limonoids, alkaloids, phenolic, polysaccharides, flavonoids, phytosterols, essential oils, and fatty acids ( Zhang et al., 2015 ). The major active ingredients are benzylisoquinoline alkaloids, including berberine, jatrorrhizine, palmatine, magnoflorine, magnocurarine, phellodendrine, and tetrahydropalmatine ( Velmurugan et al., 2017 ; Balážová et al., 2022 ; Erhan et al., 2023 ; Feng et al., 2023 ), which are commonly used as anti-inflammatory, antipyretic, and antibacterial medicines, promoting blood circulation, dysentery, diuretic, hemorrhage, and blood glucose regulating ( Kim et al., 2011 ; Steinmann et al., 2011 ; Velmurugan et al., 2017 ; Sun et al., 2019 ). The yellow, flexible, and tough wood of this medicinal plant boasts an excellent texture and can be used to create furniture and industrial art ( Sun et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…belongs to the family Rutaceae and natively grows in northern China, Korea, and Japan. It was reported that P. amurense contains rich alkaloids, including berberine, palmatine, jatrorrhizine, magnoflorine, and phellodendrine ( Mori et al., 1994 ; Xian et al., 2014 ; Wang et al., 2015 ), which exhibit various biological activities and have been widely used in clinical treatments for their antifungal ( Xiao et al., 2015 ), antibacterial ( Tsujii et al., 2020 ), anti-inflammatory ( Lee et al., 2012 ; Jung et al., 2017 ), and possible anticancer effects ( Muralimanoharan et al., 2009 ; James et al., 2011 ; Hambright et al., 2015 ; Balážová et al., 2022 ). However, the detailed microscopic distribution and roles of alkaloids in the P. amurense stem remain unclear.…”
Section: Introductionmentioning
confidence: 99%